Hubungan Karakteristik Individu Perawat dengan Insiden Keselamatan Pasien Tipe Administrasi Klinik di Rumah Sakit Umum Haji Surabaya - Aldiar Lailifah Lailifah Kurniavip; Nyoman Anita Damayanti (Universitas Airlangga, 2017)
Patient safety incidents type of clinic administration are incidents that occur in the process of patient identification, handover, agreement, informed consent, queuing, referral, admission, discharge of patients from inpatient, transfer of care, division of tasks, response of emergency. Based on patient safety incidents reports of RSU Haji, there were 12 patient safety incidents type of clinic administration (standard 0% or zero accident) during January 2014-June 2016 in inpatient unit. This research aimed to analyze the correlation between nurse’s individual characteristics with patient safety incidents type of clinic administration. This research was an observational descriptive study with cross sectional design. Questionnaires were distributed to 48 nurses that divided into 6 inpatient units. The results of this research showed that the lower the nurse's knowledge about patient safety and patient safety incidents type of clinic administration, the higher the nurse’s work fatigue, the lower the nurse’s motivation toward to the application of patient safety program, the higher the tendency of patient safety incidents type of clinic administration occured in inpatient unit of RSU Haji Surabaya. The conclusion of this research are knowledge, work fatigue, motivation of nurse have a correlation with patient safety incidents type of clinic administration in inpatient unit of RSU Haji Surabaya. Keywords: patient safety incidents, clinic administration, nurse, hospital